The Poverty Tour: Life in the Slums of Mumbai and Manila as Seen in Danny Boyle’s Slumdog Millionaire and Merlinda Bobis’s The Solemn Lantern Maker - Hanrahan, Feidhlim (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
In the twenty-first century Mumbai and Manila, lingering postcolonial issues have merged with contemporary issues of globalisation and neo-imperialism as both India and the Philippines are faced with the realities of Western hegemony. This article will examine how the creators of the film Slumdog Millionaire and the novel The Solemn Lantern Maker, both from 2008, have chosen to portray these similar realities in different ways. Two major questions could be asked about these texts. Has British director Danny Boyle fallen into the trap of Orientalism, as outlined by Said in 1978, glamorising the abject poverty of the Mumbai slums, making them look appealingly exotic under a Western gaze? Is the Philippine-Australian author Merlinda Bobis’s representation of the penury of Manila’s street children, from their huts to shopping malls, passing through an underworld of sex tourism, a more authentic representation than Boyle’s? Or is it merely a native informant’s appeal for global readership? These postcolonial texts have become commodities in a global market, where their marketing in the Western world by global media corporations affects their reception and interpretation. Keywords: Danny Boyle; Merlinda Bobis; postcolonial exotic; neo-imperialism; globalisation; poverty